2015
DOI: 10.1080/21645515.2015.1066948
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HPV prevalence between HPV-vaccinated and non-vaccinated young adult women (20–26 years)

Abstract: There is some concern about the effectiveness of the HPV vaccine among young adult women due to the risk of prior HPV infection. This study used National Health and Nutrition Examination Survey (NHANES) 2007-2012 data to evaluate the effectiveness of HPV vaccination among women 20-26 years of age who were vaccinated after 12 years of age. This cross-sectional study examined 878 young adult women (20-26 years) with complete information on HPV prevalence and HPV vaccination status from NHANES 2007-2012. Vaginal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…When comparisons of HPV vaccinated young women were made, it was found that vaccination was significantly associated with reductions in prevalence of vaccine-type HPV, although many would have potentially been exposed before receiving the vaccine. 47 In addition to demonstrating the population-level effectiveness of the vaccine among women who received it at older ages, it became clear that vaccination against other high-risk types was desirable. Estimates of the prevalence of 9vHPV types among females 14-59 years of age in the prevaccine era were found to be 16%, with disparities observed by race/ethnicity.…”
Section: Genital Hpvmentioning
confidence: 99%
“…When comparisons of HPV vaccinated young women were made, it was found that vaccination was significantly associated with reductions in prevalence of vaccine-type HPV, although many would have potentially been exposed before receiving the vaccine. 47 In addition to demonstrating the population-level effectiveness of the vaccine among women who received it at older ages, it became clear that vaccination against other high-risk types was desirable. Estimates of the prevalence of 9vHPV types among females 14-59 years of age in the prevaccine era were found to be 16%, with disparities observed by race/ethnicity.…”
Section: Genital Hpvmentioning
confidence: 99%
“…Of the 21 studies, 14 were cross-sectional, 24À37 three were retrospective cohort, 38À40 two were prospective cohort studies, 41,42 and two were experimental studies. 43,44 Nine studies were conducted in the U.S., 26,28,31,33,36,38,39,42,45 three in the United Kingdom, 34,37,41 two in Sweden, 25,30 and one each in Australia, 29 Canada, 44 Colombia, 32 Denmark, 25 France, 27 Italy, 35 Norway, 25 Peru, 6 and Uganda. 24…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Given its Vioxx history Merck's promotion of Gardasil ® as being 98% effective should awaken the senses of even the most ardent vaccine supporter. If one were to examine the clinical trial data they would instantly realize that the vaccine is far less effective than we are led to believe, even raising concerns with some researchers that it may lead to more severe infections and even an increased incidence of cervical cancer [99].…”
Section: Enter Gardasilmentioning
confidence: 99%